2016
DOI: 10.1002/hipo.22601
|View full text |Cite
|
Sign up to set email alerts
|

Beware of your Cre‐Ation: lacZ expression impairs neuronal integrity and hippocampus‐dependent memory

Abstract: Expression of the lacZ-sequence is a widely used reporter-tool to assess the transgenic and/or transfection efficacy of a target gene in mice. Once activated, lacZ is permanently expressed. However, protein accumulation is one of the hallmarks of neurodegenerative diseases. Furthermore, the protein product of the bacterial lacZ gene is ß-galactosidase, an analog to the mammalian senescence-associated ß-galactosidase, a molecular marker for aging. Therefore we studied the behavioral, structural and molecular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Golgi staining was performed as previously described (Giusti et al, 2014; Reichel et al, 2016), and to shift the staining towards glia cells instead of neurons, we adapted a modified protocol described by Ranjan and Mallick (Ranjan and Mallick, 2012). Mice were sacrificed under anesthesia, the brains carefully dissected out and briefly rinsed in dH2O, and the brains were incubated in 4% PFA-PBS at room temperature for 72 h. Subsequently the protocol of the FD Rapid GolgiStain™ Kit (FD Neurotechnologies, INC) was followed.…”
Section: Star Methodsmentioning
confidence: 99%
“…Golgi staining was performed as previously described (Giusti et al, 2014; Reichel et al, 2016), and to shift the staining towards glia cells instead of neurons, we adapted a modified protocol described by Ranjan and Mallick (Ranjan and Mallick, 2012). Mice were sacrificed under anesthesia, the brains carefully dissected out and briefly rinsed in dH2O, and the brains were incubated in 4% PFA-PBS at room temperature for 72 h. Subsequently the protocol of the FD Rapid GolgiStain™ Kit (FD Neurotechnologies, INC) was followed.…”
Section: Star Methodsmentioning
confidence: 99%
“…LacZ expression in glutamatergic neurons in the cortex, for example, causes substantial deficits in hippocampus-dependent memory, as well as structural changes of, e.g., dendrite morphology and reduction of hippocampal volume. GFP expression in the same cell populations, on the other hand, does not result in deficiencies in cognition or structure ( Reichel et al, 2016 ). Taken together, the findings of Reichel et al (2016) might explain the effect of DA cell loss in En1 lacZ/+ mice, which is not present in the En1 Cre/+ lines.…”
Section: Discussionmentioning
confidence: 99%
“…GFP expression in the same cell populations, on the other hand, does not result in deficiencies in cognition or structure ( Reichel et al, 2016 ). Taken together, the findings of Reichel et al (2016) might explain the effect of DA cell loss in En1 lacZ/+ mice, which is not present in the En1 Cre/+ lines.…”
Section: Discussionmentioning
confidence: 99%
“…Our focus has been on lacZ expression in DRG neurons; one previous study has investigated expression in cortical neurons and raised concerns regarding the use of LacZ reporters ( Reichel et al, 2016 ). The authors found that lacZ expression in cortical glutamatergic neurons caused severe morphological and behavioural impairments such as decreased hippocampal volume, reduced dendritic branching in hippocampal neurons, and deficits in hippocampus-dependent memory.…”
Section: Discussionmentioning
confidence: 99%